2014
DOI: 10.1016/j.cell.2014.01.056
|View full text |Cite
|
Sign up to set email alerts
|

S-Glutathionylation of Cryptic Cysteines Enhances Titin Elasticity by Blocking Protein Folding

Abstract: The giant elastic protein titin is a determinant factor in how much blood fills the left ventricle during diastole, and thus in the etiology of heart disease. Titin has been identified as a target of S-glutathionylation, an end product of the nitric oxide signaling cascade that increases cardiac muscle elasticity. However, it is unknown how S-glutathionylation may regulate the elasticity of titin and cardiac tissue. Here we show that mechanical unfolding of titin immunoglobulin (Ig) domains exposes buried cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
236
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(252 citation statements)
references
References 67 publications
(71 reference statements)
13
236
2
1
Order By: Relevance
“…To differentiate between the two populations, we implemented refolding experiments using a linear increasing ramp in the force (100 pN·s −1 ), or "force ramp." This technique allows us to discern the relative mechanical stability of domains in the denature and probe pulses by measuring the force at which they unfold on the ramp (27). In a representative recording of a force-ramp refolding experiment, a single FimA polyprotein is subject to three unfolding/refolding cycles alternating 1-s and 20-s quench pulses (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To differentiate between the two populations, we implemented refolding experiments using a linear increasing ramp in the force (100 pN·s −1 ), or "force ramp." This technique allows us to discern the relative mechanical stability of domains in the denature and probe pulses by measuring the force at which they unfold on the ramp (27). In a representative recording of a force-ramp refolding experiment, a single FimA polyprotein is subject to three unfolding/refolding cycles alternating 1-s and 20-s quench pulses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To measure SpaA and FimA refolding, we applied denaturequench-probe protocols using AFM-based force spectroscopy in "force-clamp" mode (26,27). On the denature pulse, a high force (≥350 pN) is applied to unfold the polyprotein, with individual events observed as ∼12.5-nm steps in the extension vs. time trace.…”
Section: Resultsmentioning
confidence: 99%
“…Although extremely simple molecular assays such as DNA or RNA hairpins could fit into a single reaction coordinate description [48], increasing slightly the complexity of the molecule leads to a dramatical rise in the complexity of the actual free energy landscape in the system, requiring more detailed studies. In this sense, molecules such as multiple nucleic-acid hairpins [53], protein-ligand complexes [54] or any mechanically pulled protein [55], appear as potential systems where a one-dimensional description takes the risk of leading to a clear misunderstanding of the actual complexity of their conformational space and the dynamical processes to which they are subject.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…3). Intradomain spectroscopic probes showed that the C1 domain exhibits some degree of folding-related dynamics, as is typical of Ig domains in muscle and similar to those found in titin (29).…”
Section: N-terminal Cmybp-c Becomes More Compact and Less Disorderedmentioning
confidence: 99%